2014
DOI: 10.12740/pp/24992
|View full text |Cite
|
Sign up to set email alerts
|

Group psychoeducation in bipolar mood disorders – the influence on the cognitive representation of the illness. The results of the program “Taming the bipolar affective disorder”

Abstract: Psychoeducation may exert a positive influence on virtually important cognitive variables, which seem to be clinically important. This influence may disappear with time, thus the interventions should either be repeated or the duration of intervention should be prolonged. The study shows new possible research directions in the field of searching for the mechanism of action of psychoeducation in bipolar disorder, as well as of its active components.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…However, there is an unmet need for studies which would look into this aspect in patients with bipolar disorders. In our earlier study without a control group, there was a 6.5% rise in the results of the KNS-UZR scale directly after psychoeducation [7]. Both the result we observed before and the change in this aspect observed in the present study point to the need for further studies which would analyze the relationship between observed changes and clinical variables.…”
Section: Psychoeducation and Hope For Successsupporting
confidence: 57%
See 4 more Smart Citations
“…However, there is an unmet need for studies which would look into this aspect in patients with bipolar disorders. In our earlier study without a control group, there was a 6.5% rise in the results of the KNS-UZR scale directly after psychoeducation [7]. Both the result we observed before and the change in this aspect observed in the present study point to the need for further studies which would analyze the relationship between observed changes and clinical variables.…”
Section: Psychoeducation and Hope For Successsupporting
confidence: 57%
“…French researchers observed that in patients diagnosed with bipolar disorders who took part in psychoeducation there was a significant increase in external locus of control, which was interpreted as a rise in trust towards healthcare staff [19]. However, in our earlier studies, which were based on the same intervention but conducted without a control group, we did not observe a statistically significant influence of psychoeducation on any aspect of locus of health control, even though the mean values for both internal and external locus of control in the participants increased [7]. The increase in the internal locus of control in the study group directly after the intervention in the present study may suggest a possibility of achieving a health-promoting change in this area.…”
Section: Psychoeducation and The Locus Of Health Controlmentioning
confidence: 59%
See 3 more Smart Citations